The seroprevalence of human papillomavirus by immune status and by ethnicity in London - Casabonne, Delphine (BioMed Central, 2009)
BACKGROUND: The natural history of cutaneous HPV is unclear and in particular, seroprevalence among individuals with different levels of immune function and ethnicity is unknown. As part of a study of cutaneous squamous cell carcinoma (SCC) and HPV among organ transplant recipients (OTR) from London, we investigated the seroprevalence and risk factors for 34 HPV types (detected using Luminex technology) among 409 OTR patients without skin cancer (243 Caucasians and 166 non-Caucasians), 367 individuals with end stage renal failure on dialysis (222 Caucasians and 145 non-Caucasians) and 152 immunocompetent (IC) individuals without skin cancer (102 Caucasians and 50 non-Caucasians) to compare the HPV seroprevalence in patients with differing immune status and ethnicity. In total, seroprevalence data from 928 individuals, all from London, was available. RESULTS: Overall, no difference between HPV seroprevalence by immune status was observed (P = 0.3) among Caucasian or among non-Caucasian individuals, with seroprevalence varying from 87% to 94% across different immune status and ethnic groups. Those individuals seropositive to multiple types of one genus were more likely to be seroreactive to multiple types of another genus, independent of immune status or ethnicity. Lower seroprevalence for gammaHPV 4, and to a lesser extent gammaHPV 48, were observed among OTR compared to IC and dialysis patients. Higher seroprevalence against antibodies to betaHPV 93 were detected more frequently in non-Caucasians than Caucasians whereas muHPV 1 and, to a lesser extent, gammaHPV 4 were found more frequently among Caucasians - these findings were independent of immune status. Within non-Caucasian subgroups, the seroprevalence of 8 HPV (alpha-mucosal HPV16 and 13, alpha-cutaneous HPV7 and 2, betaHPV8, 17, 23 and 38) was significantly (P < 0.02) higher in Black compared to Asian patients. HPV16 being sexually transmitted, this might suggest a potential sexual route of transmission for some beta HPV types. CONCLUSION: We did not observe major disturbance in antibody response between immunocompetent, dialysis and OTR individuals, but significant differences in HPV seroprevalence were identified according to ethnicity. Further research is needed to clarify the natural history of cutaneous HPV, particularly given the growing research interest in its possible role in the pathogenesis of cutaneous SCC.